The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/su151813516
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Ergonomic Workplace: Fostering Job Satisfaction and Productivity among Business Process Outsourcing (BPO) Workers

Ma. Janice J. Gumasing,
Emil Renfred A. Rendon,
Josephine D. German

Abstract: The business process outsourcing (BPO) sector is important in managing business especially in a developing country like the Philippines. Call centers are one of the most common type of industries within the BPO sector as they generate 75.1% of its revenues. Given the lack of studies regarding the ergonomic factors in the BPO industry, the goal of this research is to examine the relationships of different ergonomic domains on the job satisfaction and overall productivity of the BPO agents in a customer service … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 114 publications
0
0
0
Order By: Relevance
“…According to the study of [27] there is positive relationship between workplace ergonomics and employees performance in a private security firms; therefore the firm should consider ergonomic improvements to create healthier and more productive engaged workforce, which can have cascading effects in multiple organization aspects. Also, [31] found that macro-ergonomics and physical ergonomics significantly increase job satisfaction and overall productivity.…”
Section: Skills Factorsmentioning
confidence: 95%
“…According to the study of [27] there is positive relationship between workplace ergonomics and employees performance in a private security firms; therefore the firm should consider ergonomic improvements to create healthier and more productive engaged workforce, which can have cascading effects in multiple organization aspects. Also, [31] found that macro-ergonomics and physical ergonomics significantly increase job satisfaction and overall productivity.…”
Section: Skills Factorsmentioning
confidence: 95%